Association of glutathione S-transferases (GSTT1, GSTM1 and GSTP1) genes polymorphisms with nonalcoholic fatty liver disease susceptibility: A PRISMA-compliant systematic review and meta-analysis. Issue 38 (23rd September 2022) - Zhu, Yi; Yang, Jian-Hua; Hu, Jun-Ping; Qiao, Ming
Abstract : Background: Glutathione S-transferases ( GSTs ) genes single-nucleotide polymorphisms (SNPs) have been connected with the susceptibility of nonalcoholic fatty liver disease (NAFLD), but with inconsistent results across the current evidences. The present work was schemed to explore the association between GSTs genes polymorphisms and the NAFLD vulnerability via meta-analysis. Methods: PubMed, Web of Science, Cochrane Library, China National Knowledge Infrastructure and Wanfang were retrieved for eligible literatures previous to March 10, 2021. The odds ratio (OR) of the dichotomic variables and the standardized mean difference of quantitative variables with corresponding 95% confidence intervals (95%CIs) were computed to evaluate the strength of the associations. The quality of included studies were assessed via using Newcastle-Ottawa Scale (NOS). Results: In total, 7 case-control studies encompassing 804 NAFLD patients and 1362 disease-free controls in this meta-analysis. Ultimately, this analysis included 6, 5 and 5 studies for GSTM1, GSTT1 and GSTP1 polymorphisms, respectively. The pooled data revealed that the GSTs genes SNPs had conspicuous associations with NAFLD susceptibility: for GSTM1, null versus present, OR = 1.46, 95%CI 1.20 to 1.79, P = .0002; for GSTT1, null versus present, OR = 1.34, 95%CI 1.06 to 1.68, P = .01; for GSTP1, Ile/Val or Val/Val versus Ile/Ile, OR = 1.60, 95%CI 1.23 to 2.09, P = .0005. Conclusion: This work revealed that the GSTM1 null, GSTT1 null and GSTP1 -Val genotypes might be related to increased NAFLD susceptibility.